Problematika Pembelajaran Pendidikan Pancasila Dan Kewarganegaraan Kelas VII.E Di SMP Negeri 7 Muaro Jambi - Simamora, Lestari Wulandari; Salam, M.; Usmanto, Heri Usmanto; Simaremare, Tohap Pandapotan (Civic Education Perspective Journal, 2021)
Abstract: The results of the initial observations of this study were the teacher's obstacles in the implementation and learning activities of Civics in grade VII which were accompanied by low student cognitive learning outcomes. This study was conducted with the aim of describing the problems of learning Pancasila and citizenship education for class VII.E at SMP Negeri 7 Muaro Jambi. The research method used in this research is descriptive qualitative. Data and data sources were obtained from informants, namely PPKn teachers who teach in class VII.E and 10 students in class VII.E with data collection techniques in the form of interviews, observations, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. Based on the results of data analysis that has been carried out, the findings and conclusions of the results of this study are as follows: First, on planning activities. The problem that occurs is the difficulty of teachers in preparing RPP in accordance with the principles of RPP preparation. Second, on implementation activities. The problems that occur are a) the teacher has difficulty controlling the condition of class VII.E in the last lesson, b) the ability to understand and think critically of class VII.E students is still low, c) lack of availability of PPKn learning media. Third, on the assessment of learning outcomes. The problems that occur are a) the teacher does not assess attitudes and skills, b) the cognitive learning outcomes of class VII.E students in PPKn subjects